Clustering analysis of 100-year international seismic catalogue for Azerbaijan - Т.Х. Бабаев; Я.Н. Алиев; Г.Р. Бабаев (Геология и геофизика Юга России, 2025)
Relevance. Azerbaijan is tectonically situated in the Arabian-Eurasian continent collision zone. Due to this collision activity the seismic pattern of the region is observed with the occurrence of frequent moderate and occasionally strong earthquakes. Research methods. In this study, we used a catalog of International Seismological Centre through the Azerbaijan region including the neighbor parts and aquatory (Caspian Sea). Catalog has been clustered according to the 6 tectonic mega-zones of Azerbaijan. Aim. The purpose of this paper is to expose the seismicity level of Azerbaijan employing the international catalog of earthquakes from 1926 to 2022. Results. We estimated the seismicity indicators for each cluster. a- and b-values of Gutenberg-Richter law have been evaluated for each cluster. We examined the precision of them computing the maximum magnitude uncertainty and the results seem to be precise enough where the maximum magnitude uncertainty values are close to 0. We defined magnitude of completeness around or above 4 for the clusters and the bin was defined 0.1 for each. The highest a- and b-values are observed in cluster I (GusarShabran and aquatory) and cluster VI (Talysh mountains and aquatory). a-, b- values for cluster I are 6.97 and 1.16 respectively and for cluster VI are 11.89 and 2.17 respectively. The number of earthquakes with magnitude greater and equal to magnitude of completeness for cluster I and VI is 213 and 30 respectively. For cluster II, III, IV, V the number of earthquakes (M ≥ Mc) are 399, 115, 318, 503 respectively. Conclusions. The seismic activity for each tectonic segment has been demonstrated in terms of the number of earthquakes with magnitude greater than 3.8, at least.